Mise en œuvre concertee et solidaire du Traite sur les ressources phytogenetiques et du Protocole de Nagoya : Abecedaire pour points focaux nationaux et autres parties prenantes - Halewood, Michael (Bioversity International, 2015)
The overall objective of this report – and the survey, workshop and follow-up analysis upon which it is based - is to provide national policy actors with a tool to increase their ability and confidence to implement the CBD/NP and ITPGRFA/MLS in mutually supportive ways.